Pyrotinib targeted EGFR/GRP78 mediated cell apoptosis in high EGFR gene copy number gastric cancer - Lingbo Bao; Xudong Wang; Xiuyong Liao; Dong Li; ChunXue Li; Nan Dai; Xiaoyan Dai; Jing Yang; Nana Hu; Xueling Tong; Zhenjie He; Yuancheng Zhao; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Despite frequent Epidermal Growth Factor Receptor (EGFR) amplification and overexpression in gastric cancer, limited therapeutic responses were observed in existing EGFR-targeted agents. Pyrotinib, an irreversible dual EGFR/HER2 tyrosine kinase inhibitor, has shown clinical efficacy in HER2-driven malignancies, but its potential role in EGFR-high copy number gastric cancer remains to be investigated. Methods Using EGFR-high copy number gastric cancer cell lines, primary cells and subcutaneous tumor models in nude mice, we systematically evaluated pyrotinib’s anti-tumor activity through viability assays, apoptosis analysis, and transcriptomic profiling. Mechanistic studies included co-immunoprecipitation, proximity ligation assays, ubiquitination assays, and RNA sequencing. Results Pyrotinib selectively suppressed proliferation, induced apoptosis, and chemosensitized in EGFR-high copy number gastric cancer models. Mechanistically, pyrotinib promoted EGFR-GRP78 (Glucose-regulated protein 78) complex formation in the endoplasmic reticulum, activating the protein kinase R-like endoplasmic reticulum kinase/ activating transcription factor 4/ C-EBP homologous protein (PERK/ATF4/CHOP) axis to drive ER stress-mediated apoptosis. Concurrently, pyrotinib inhibited GRP78 phosphorylation at Thr62, triggering K48-linked ubiquitination (ubiquitin chains formed via lysine 48 linkages) and proteasomal degradation, which impaired DNA double-strand break (DSB) repair and sensitized cells to oxaliplatin-induced γ-H2A.X accumulation. Conclusion This translational study suggests that pyrotinib combined with oxaliplatin may serve as a promising strategy for patients with EGFR-high copy number gastric cancer and highlighted the discovery of this previously unknown EGFR/ GRP78 signaling axis, which provides the molecular basis and the rationale to target EGFR.